Application of coupled neural oscillators for image texture segmentation and modeling of biological rhythms - Strumiłło, Paweł; Strzelecki, Michał (Zielona Góra: Uniwersytet Zielonogórski)
The role of relaxation oscillator models in application fields such as modeling dynamic systems and image analysis is discussed. A short review of the Van der Pol, Wilson-Cowan and Terman-Wang relaxation oscillators is given. The key property of such nonlinear oscillators, i.e., the oscillator phase shift (called the Phase Response Curve) as a result of external pulse stimuli is indicated as a fundamental mechanism to achieve and sustain synchrony in networks of coupled oscillators.
Keywords: biological rhythms; nonlinear oscillations; networks of synchronised oscillators; texture segmentation; cardiac pacemakers